2020
DOI: 10.1186/s12866-020-1712-3
|View full text |Cite
|
Sign up to set email alerts
|

PilG and PilH antagonistically control flagellum-dependent and pili-dependent motility in the phytopathogen Xanthomonas campestris pv. campestris

Abstract: Background: The virulence of the plant pathogen Xanthomonas campestris pv. campestris (Xcc) involves the coordinate expression of many virulence factors, including surface appendages flagellum and type IV pili, which are required for pathogenesis and the colonization of host tissues. Despite many insights gained on the structure and functions played by flagellum and pili in motility, biofilm formation, surface attachment and interactions with bacteriophages, we know little about how these appendages are regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Swarming motility was determined on NY plates containing 2% glucose and 0.6% agar. Swimming motility was assessed on 0.28% agar plates containing 0.03% Bacto peptone and 0.03% yeast extract as described previously (Qi et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Swarming motility was determined on NY plates containing 2% glucose and 0.6% agar. Swimming motility was assessed on 0.28% agar plates containing 0.03% Bacto peptone and 0.03% yeast extract as described previously (Qi et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…This disease is one of the most widespread and destructive in the world, with an economic impact in many geographical areas, comprising Brazil, Ethiopia, South Africa, Belgium, Germany, Sweden, France, Netherlands, Italy, United States, United Kingdom, Nepal, China, Taiwan, Canada, Australia, and India [3]. Xcc infection is particularly harmful and difficult to control due to the numerous virulence factors that characterize the bacterium that, specifically, has a single polar flagellum that allows the bacterium, once inoculated, and penetrated the plant, to move and reach the vascular system [4]. Xcc has developed a unique quorum sensing system, which plays a key role in regulating the biosynthesis of bacterial virulence factors [5].…”
Section: Introductionmentioning
confidence: 99%
“…In our earlier work, we aimed to investigate the functions of these SD‐RRs in Xcc; therefore, we constructed a series of insertional mutants using a suicide vector (pK18 mob ) strategy (Schäfer et al, 1994). In previous work we screened these mutants for influence on cell motility and showed that several of them influenced motility, including disruptions to the known regulators CheY and VemR (Li et al, 2020; Qi et al, 2020). Interestingly, insertional mutant strain 1966nk, which derived from the disruption of the ORF XC_1966 (hereafter named mcvR ) in the genome of Xcc strain 8004 (accession number CP000050), had reduced swimming ability when compared with the wild‐type Xcc strain.…”
Section: Resultsmentioning
confidence: 99%